2016
DOI: 10.1245/s10434-016-5308-y
|View full text |Cite|
|
Sign up to set email alerts
|

Fertility in Women of Reproductive Age After Breast Cancer Treatment: Practice Patterns and Outcomes

Abstract: In treating young breast cancer patients, it is important to assess fertility desire, discuss treatment risks relating to fertility, and discuss preservation options. Although not every woman in this group desired pregnancy, 71/80 (89 %) women having a documented FD sought further fertility consultation and options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 44 publications
1
18
5
1
Order By: Relevance
“…Among female survivors surveyed as part of a cohort of adolescent and young adult survivors identified through a Surveillance, Epidemiology, and End Results linkage, fewer than one‐half stated that strategies to preserve their fertility were discussed prior to the initiation of treatment . Other recent reports have found similarly low rates of attention to fertility, although some have found rates as high as 85% . The study that to our knowledge reported the highest rate of attention included only patients seen at National Cancer Institute‐designated comprehensive cancer centers, although the results of the current study did not demonstrate a difference in attention to fertility between community and academic sites …”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Among female survivors surveyed as part of a cohort of adolescent and young adult survivors identified through a Surveillance, Epidemiology, and End Results linkage, fewer than one‐half stated that strategies to preserve their fertility were discussed prior to the initiation of treatment . Other recent reports have found similarly low rates of attention to fertility, although some have found rates as high as 85% . The study that to our knowledge reported the highest rate of attention included only patients seen at National Cancer Institute‐designated comprehensive cancer centers, although the results of the current study did not demonstrate a difference in attention to fertility between community and academic sites …”
Section: Discussioncontrasting
confidence: 71%
“…18 Other recent reports have found similarly low rates of attention to fertility, although some have found rates as high as 85%. [19][20][21][22] The study that to our knowledge reported the highest rate of attention included only patients seen at National Cancer Institutedesignated comprehensive cancer centers, although Cancer June 1, 2019 the results of the current study did not demonstrate a difference in attention to fertility between community and academic sites. 21 In a representative, Swedish, population-based study of survivors diagnosed between the ages of 18 and 40 years from 2003 through 2007, approximately 48% reported that they received information regarding the impact of treatment on fertility, and 14% reported that they received information concerning fertility preservation.…”
Section: Discussioncontrasting
confidence: 50%
“…There remains a significant lack of reproductive counseling prior to breast cancer treatment initiation worldwide [ 13 ]. Many women are unaware that their chances of future parenthood might be affected by hormonal therapy or chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, a recent study published in October 2016 and conducted at the Cleveland Clinic between 2006 and 2014 showed that less than one-third of women had a documented fertility discussion with their physician prior to treatment. Of those who did receive documented counseling, nearly 90% sought some form of fertility preservation, demonstrating the massive impact of formal education sessions on cancer patients’ childbearing choices [ 13 ]. Potential barriers to fertility counseling include physicians’ level of knowledge about fertility preservation, attitudes and comfort level with the topic, patient preferences, and financial obstacles [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation